Canadian Stroke Best Practice Recommendations: Mood, Cognition and Fatigue following Stroke Practice Guidelines, Update 2015. Issue 7 (October 2015) - Eskes, Gail A.; Lanctôt, Krista L.; Herrmann, Nathan; Lindsay, Patrice; Bayley, Mark; Bouvier, Laurie; Dawson, Deirdre; Egi, Sandra; Gilchrist, Elizabeth; Green, Theresa; Gubitz, Gord; Hill, Michael D.; et al.
Every year, approximately 62 000 people with stroke and transient ischemic attack are treated in Canadian hospitals, and the evidence suggests one-third or more will experience vascular-cognitive impairment, and/or intractable fatigue, either alone or in combination. The 2015 update of the Canadian Stroke Best Practice Recommendations: Mood, Cognition and Fatigue Module guideline is a comprehensive summary of current evidence-based recommendations for clinicians in a range of settings, who provide care to patients following stroke. The three consequences of stroke that are the focus of the this guideline (poststroke depression, vascular cognitive impairment, and fatigue) have high incidence rates and significant impact on the lives of people who have had a stroke, impede recovery, and result in worse long-term outcomes. Significant practice variations and gaps in the research evidence have been reported for initial screening and in-depth assessment of stroke patients for these conditions. Also of concern, an increased number of family members and informal caregivers may also experience depressive symptoms in the poststroke recovery phase which further impact patient recovery. These factors emphasize the need for a system of care that ensures screening occurs as a standard and consistent component of clinical practice across settings as stroke patients transition from acute care to active rehabilitation and reintegration into their community. Additionally, building system capacity to ensure access to appropriate specialists for treatment and ongoing management of stroke survivors with these conditions is another great challenge.